A comparison of various double loops frequency selective surfaces in terms of angular stability - Mohamed Nafis, Nur Biha; A. Rahim, Mohamad Kamal; Ayop, Osman; Zubir, Farid; A Majid, Huda
This paper presents the comparison of Frequency Selective Surfaces (FSS) structure performance based on three different double loops: square, circular and hexagonal structures. The simulation process of the double loops FFS structures are carried out by using the Computer Simulation Technology (CST) Microwave Studio software. The dielectric substrate used in the simulation is the FR-4 lossy substrate (